Partisipasi Masyarakat dalam Pencegahan Narkoba melalui Program Pencegahan Pemberantasan Penyalahgunaan dan Peredaran Gelap Narkoba (P4GN) - Fatya Azzahra; All Fine Loretha (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Drug abuse is a serious threat that impacts social stability and public health. This study aims to analyze the forms of community participation in the Prevention and Eradication of Drug Abuse and Illegal Drug Trafficking (P4GN) program, particularly in the RT.05 Pondok Bambu area of East Jakarta. The approach used is a qualitative approach with methods of interviews, observation, and documentation. Informants consist of representatives from the National Narcotics Agency (BNN RI), community leaders, and local residents selected through purposive sampling. The results of the study indicate that community participation in the decision-making dimension remains low, participation in implementation is incidental, while the benefits of P4GN efforts are beginning to be felt in the form of increased awareness and environmental safety. Community evaluation is conducted informally but has the potential to be developed further. This study emphasizes that the success of the P4GN program heavily depends on strong partnerships between the community and relevant institutions, as well as the need for strengthened education, training, and more systematic participation opportunities.